Children and Demand: Direct and Non-direct Effects. - Browning, M; Lechene, V (2003)
This paper examines the effects of children on demands. We employ a French family expenditure survey that has a number of unusual features to explore the source of the correlation between children and demands. The first sample we use is of older households which has information on completed fertility. The second sample is of Younger households for whom we have family background variables. We find that children are not exogenous for some goods. These findings cast doubt on the usual practice of identifying "direct" children effects with the coefficients on the children variables in demand equations.